ORGANIZATION OF COMPREHENSIVE SECURITY MEASURES FOR CRITICAL INFRASTRUCTURE FACILITIES BY THE SECURITY AND DEFENSE FORCES OF UKRAINE - Nazarenko, Oleh; Hodlevskyi, Serhii; Skakalin, Ihor (Honor and Law, 2025)
Key approaches to camouflage and equipping important state facilities and critical infrastructure facilities under martial law with engineering and engineering means are considered, taking into account the experience of their use by units of the Security and Defense Forces of Ukraine to ensure state security. Particular attention is paid to the principles of integration of natural and artificial elements of camouflage with engineering and technical means of protection, as well as the organization of security, taking into account the conduct of reconnaissance by the enemy in various ways and means to identify the locations of important state facilities and critical infrastructure facilities. Within the framework of the study, the problems of interaction between various components of the Security and Defense Forces of Ukraine in the process of protecting important state facilities and critical infrastructure facilities are highlighted.